Analisis Nilai Sosial Dalam Tradisi Betanam Dan Setulungan Ngetam Padi Pada Masyarakat Desa Tanjung Ganti 2 Kabupaten Kaur - Harjuni, Miki; Kasmantoni, Kasmantoni; Friantary, Heny (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
The purpose of this study is to discuss the social values in the betanam and setulungan ngetam padi traditions in the Tanjung Ganti 2 village community and the procession of the betanam and setulungan ngetam padi traditions. This research is motivated because the Tanjung Ganti 2 village community still has the betanam and setulungan ngetam padi tradition and of course it has its uniqueness. With this research to find out the social values in the tradition of Betanam and Setulungan Ngetam Padi and increase insight into the procession of the Betanam and Setulungan Ngetam Padi tradition in the community of Tanjung Ganti 2 village, Kaur district. This study uses descriptive qualitative research. Data sources obtained from the Village Head, Village Secretary, Village Imam, BPD Chairperson, Customary Chairperson and Customary Members of Tanjung Ganti 2 Village. The data obtained are in the form of observation data, interview results, documentation in Tanjung Ganti 2 Village, Kaur District. The results of this study reveal that the social values in the Betanam and Setulungan Ngetam Padi tradition in the community of Tanjung Ganti 2 village, Kaur district are as follows: personality values, material values, biological values, legal compliance values, knowledge values, religious values and beauty values as well as regarding the procession of the Betanam and Setulungan Ngetam Padi tradition in Tanjung Ganti 2 village which has its own uniqueness and differences with traditions from other regions.